2018
DOI: 10.2147/copd.s153525
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between exercise capacity and different functional markers in pulmonary rehabilitation for COPD

Abstract: RationaleThe relationship of functional parameters such as lung mechanics, chest kinematics, metabolism and peripheral and respiratory muscle function with the level of exercise tolerance remains a controversial subject. While it has been previously shown that pulmonary rehabilitation is capable of improving exercise tolerance in patients afflicted by COPD, as expressed by values of 6-minute walking test (6MWT), the degree of contribution to this change by each of the aforementioned parameters remains unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 34 publications
6
59
0
4
Order By: Relevance
“…This study shows that, as already reported other sedentary populations [5][6][7][8] This study is part of a wider study investigating the effects of exercise training at the level of VT 1 and one of the fi ndings was that VO 2max declined by 16.4%, over 1 year without training while this decline was prevented by training. Although it is well accepted that diabetes is a progressive disease [23], such a rapid decline highlights the "vicious circle" of a sedentary lifestyle in chronic diseases [24], and characterized by rapid deterioration even at the stage of disease where patients are comparatively healthy.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This study shows that, as already reported other sedentary populations [5][6][7][8] This study is part of a wider study investigating the effects of exercise training at the level of VT 1 and one of the fi ndings was that VO 2max declined by 16.4%, over 1 year without training while this decline was prevented by training. Although it is well accepted that diabetes is a progressive disease [23], such a rapid decline highlights the "vicious circle" of a sedentary lifestyle in chronic diseases [24], and characterized by rapid deterioration even at the stage of disease where patients are comparatively healthy.…”
Section: Discussionsupporting
confidence: 83%
“…Since it has been widely studied and validated in chronic pathologies associated to sedentary lifestyles [5][6][7][8], it appears to be logically more and more employed in diabetes studies [9]. However, the basis for this use was until recently poorly documented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The performances using their cutoff values demonstrated that the two STSTs are good tools for predicting a poor 6MWD (<350 m). Nevertheless, in addition to having a strong relationship with elements of a patient’s health status, including poor exercise tolerance 30 , 31 and poor pulmonary function, 12 , 32 and reflecting the response to pulmonary rehabilitation, 33 , 34 the role of 6MWT has been demonstrated in predicting long-term mortality 35 and quality of life 12 and in indicating the need for long-term oxygen therapy 36 in COPD patients. The 5STS and 30STS may have potential capacity to predict poor prognosis because 6MWD <350 m is a predictor for high mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Patients performed a complex pulmonary rehabilitation programme with chest wall-stretching, controlled breathing techniques and training, as well as personalized exercise training 2-3 times for 20-30 minutes per day by cycling and treadmill for 4 weeks (28)(29)(30)(31). 6MWD (23), lung function (22), CWE (24), GS (27), MIP (25) and BHT (26) were measured.…”
Section: Rehabilitation Programmentioning
confidence: 99%